2013
DOI: 10.1007/s11274-013-1272-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of red wine fermentation oenological additives on inoculated strain implantation

Abstract: Pure selected cultures of Saccharomyces cerevisiae starters are regularly used in the wine industry. A survey of S. cerevisiae populations during red wine fermentations was performed in order to evaluate the influence of oenological additives on the implantation of the inoculated strain. Pilot scale fermentations (500 L) were conducted with active dry yeast (ADY) and other commercial oenological additives, namely two commercial fermentation activators and two commercial tannins. Six microsatellite markers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…; Duarte et al . ). Briefly, microsatellites were amplified in two multiplex reactions: one containing 0·05 pmol of each ScAAT1 and ScAAT6 primer pairs as well as 0·03 pmol of ScAAT4 primer pair, and another containing 0·05 pmol of ScAAT2, 0·1 pmol of ScAAT3 and 0·075 pmol of ScAAT5 primer pairs.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Duarte et al . ). Briefly, microsatellites were amplified in two multiplex reactions: one containing 0·05 pmol of each ScAAT1 and ScAAT6 primer pairs as well as 0·03 pmol of ScAAT4 primer pair, and another containing 0·05 pmol of ScAAT2, 0·1 pmol of ScAAT3 and 0·075 pmol of ScAAT5 primer pairs.…”
Section: Methodsmentioning
confidence: 97%
“…Then, mtDNA purified and cleaved with HinfI (overnight, 37°C) and the restriction pattern was analysed in agarose gel. The amplification of microsatellite loci as molecular markers for S. cerevisiae (ScAAT1, ScAAT2, ScAAT3, ScAAT4, ScAAT5 and ScAAT6) was performed as previously described (Schuller et al 2005;Duarte et al 2013). Briefly, microsatellites were amplified in two multiplex reactions: one containing 0Á05 pmol of each ScAAT1 and ScAAT6 primer pairs as well as 0Á03 pmol of ScAAT4 primer pair, and another containing 0Á05 pmol of ScAAT2, 0Á1 pmol of ScAAT3 and 0Á075 pmol of ScAAT5 primer pairs.…”
Section: Molecular Characterization Of Selected Strainsmentioning
confidence: 99%
“…In the first winery, where the oenologist carefully managed only one starter culture and did not make any spontaneous fermentation, the commercial strain always mastered the process; conversely, in the second winery, where the oenologist performed also spontaneous fermentation, the starter culture did not even take over the dominance and a continuous succession of indigenous strains overcame without one prevailed on the others. Recently, some authors ( Duarte et al, 2013 ) have hypothesized that some oenological additives, such as tannins and fermentation activators, can affect the starter implantation. García-Ríos et al (2014) carried out a preliminary approach in order to study the fitness advantages of four commercial wine yeast strains (PDM, ARM, RVA, and TTA) against some important oenological parameters, such as nitrogen concentration of grape must, fermentation temperature profile, and ethanol tolerance, which can exert strong stresses on the inoculated strain and determine its competitive advantage.…”
Section: S Cerevisiae / S Cerevisiae Inmentioning
confidence: 99%
“…To evaluate the use of starter cultures, initial studies have been conducted on the laboratory scale despite the burden that this may introduce in scaling up the results to the winery level. Recent winery-based studies have shown very interesting results on the presence and/or dominance of indigenous versus commercial S. cerevisiae strains [1][2][3][4][5][6][7]. Scholl et al investigated the presence of commercial S. cerevisiae strains in spontaneous fermentations at wineries that conduct both inoculated and spontaneous fermentations and showed that indigenous S. cerevisiae strains were found in relatively low abundance [5].…”
Section: Introductionmentioning
confidence: 99%
“…Simple sequence repeat (SSR) markers are powerful biomolecular tools for the differentiation of yeast strains [17]. The development of these techniques has led to the study of population dynamics during fermentation and has opened the possibility to understand the complex roles of microorganisms in wine fermentation [1,18].…”
Section: Introductionmentioning
confidence: 99%